2016
DOI: 10.18632/oncotarget.10717
|View full text |Cite
|
Sign up to set email alerts
|

IRF3 is an important molecule in the UII/UT system and mediates immune inflammatory injury in acute liver failure

Abstract: The urotensin II/urotensin receptor (UII/UT) system can mediate inflammatory liver injury in acute liver failure (ALF); however; the related mechanism is not clear. In this study, we confirmed that lipopolysaccharide/D-galactosamine (LPS/D-GalN) induced up-regulation of liver interferon regulatory factor 3 (IRF3) in ALF mice, whereas the UT antagonist urantide inhibited the up-regulated liver IRF3. LPS stimulation induced IRF3 transcription and nuclear translocation and promoted the secretion of interleukin-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…AMs. IRF3 is also an important transcription factor in cells and serves a role in the post-transcriptional regulation of the proinflammatory cytokines TNF-α and IL-1β (23). In addition, the authors examined the phospho-IRF-3 protein level in nuclear extracts by using western blot analysis to detect the influence of PALM3 on LPS-induced IRF-3 activation.…”
Section: Effect Of Palm3 On the Irf3 Activity In Lps-stimulated Ratmentioning
confidence: 99%
“…AMs. IRF3 is also an important transcription factor in cells and serves a role in the post-transcriptional regulation of the proinflammatory cytokines TNF-α and IL-1β (23). In addition, the authors examined the phospho-IRF-3 protein level in nuclear extracts by using western blot analysis to detect the influence of PALM3 on LPS-induced IRF-3 activation.…”
Section: Effect Of Palm3 On the Irf3 Activity In Lps-stimulated Ratmentioning
confidence: 99%
“…The urotensin II (UII)/urotensin receptor (UT) system is composed of UII and its specific receptor G protein-coupled receptor (GPR14) or UT, and is present in the liver ( 9 ), heart ( 10 ), kidney ( 11 ) and other organs. The UII/UT system has a variety of biological effects, such as inducing contraction, expanding blood vessels and influencing metabolism ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Urantide is the most effective UII receptor antagonist as it has fewer side effects and is 50–100 times more potent than other compounds ( 10 , 18 ). Previous studies have shown that urantide could antagonize the expression of UII/UT system components, thereby effectively alleviating ALI and inhibiting the proliferation of Kupffer cells ( 9 , 19 ). However, to the best of our knowledge, there has been no relevant report on whether the antagonistic UII/UT system affects the MAPK signalling pathway in preventing liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction consisted of a mixture of 10 µl SYBR-Green, 3 µl cDNA template, 1 µl each of both the forward and reverse primers against IFN-β (forward, CAACTTGCTTGGATTCCTACAAAG and reverse primer, TATTCAAGCCTCCCATTCAATTG); IRF3 (forward, CGGAAAGAAGTGTTGCGGTTAG and reverse primer, TTTGCCATTGGTGTCAGGAGAG); and β-actin (forward, CCTGGCACCCAGCACAAT and reverse primer, GCCGATCCACACGGAGATCT), and 5 µl free deionised diethylpyrocarbonate D.W. to a final volume of 20 µl. The sequences of the primers are based on previous studies (28,29).…”
Section: Methodsmentioning
confidence: 99%